2022
DOI: 10.1111/csp2.12771
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of public and private land to protect species at risk habitat

Abstract: Conservation budgets are limited, requiring strategic prioritization among actions to efficiently protect species. Systematic prioritization approaches typically determine locations for conservation that most effectively balance species protection with cost. Proxies for cost are frequently used in prioritizing land for protection. Here, we combine financial cost estimates for private land acquisition and species habitat models into a spatial prioritization to explore cost-effective habitat protection, using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…A lack of protection was also evident for hotspots of biodiversity and carbon globally (Soto-Navarro et al, 2020) and in Asia (Zhu et al, 2021). Similarly, Proctor et al (2022) found that 50% of species at risk in Ontario had less than 10% of their habitat protected by existing protected areas. A recent temporal analysis by Maxwell et al (2020) revealed that expansion of protected areas (between 2010 and 2019) made minimal contributions to conserving various elements of biodiversity and ecosystem services, including carbon storage and connectivity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A lack of protection was also evident for hotspots of biodiversity and carbon globally (Soto-Navarro et al, 2020) and in Asia (Zhu et al, 2021). Similarly, Proctor et al (2022) found that 50% of species at risk in Ontario had less than 10% of their habitat protected by existing protected areas. A recent temporal analysis by Maxwell et al (2020) revealed that expansion of protected areas (between 2010 and 2019) made minimal contributions to conserving various elements of biodiversity and ecosystem services, including carbon storage and connectivity.…”
Section: Discussionmentioning
confidence: 97%
“…Addition of protected and conserved areas within this corridor could provide significant benefits to the transboundary movement of wildlife between Algonquin Park in Ontario, Canada, and Adirondack Park in New York State, USA. Additionally, Proctor et al ( 2022 ) found that protection of species at risk habitat in Ontario may be most cost effective in the central region of the province where land cost is low, but species at risk richness is still relatively high. This aligns with areas important for connectivity and forest carbon storage identified by our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This results in higher relative cost efficiency of conservation gains in the Central and South Coasts under the landholder informed approach (SM4). The implications of this are that default use of proxies for cost (for example (Strassburg et al 2019) and (Proctor et al 2022)) that do not account for how landholder preferences influence the true cost of conservation investments are likely to result in poor conservation outcomes (Bode et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the southern part of the province, we identified spatial congruence between forest carbon and connectivity coinciding with the known Algonquin to Adirondacks Corridor (A2A). Addition of protected and conserved areas within this corridor could provide significant benefits to the transboundary movement of wildlife between Algonquin Park in Ontario, Canada, and Adirondack Park in New York State, U.S.A. Additionally, Proctor et al (2022) found that protection of species at risk habitat in Ontario may be most cost effective in the central region of the province where land cost is low, but species at risk richness is still relatively high. This aligns with areas important for connectivity and forest carbon storage identified by our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…While restoration efforts (e.g., reforestation of mixed, native forests) provide meaningful biodiversity benefits (Wang, Zhang, Li, & Wu, 2021) and increase carbon sequestration and storage (Lewis, Wheeler, Mitchard, & Koch, 2019), proactively conserving large intact ecosystems with high ecological integrity should remain a focus (Cook-Patton et al, 2021; Grantham et al, 2020; Locke et al, 2019; Noon et al, 2021). Protection of intact ecosystems can be more cost effective than restoration of degraded habitats (Cook-Patton et al, 2021; Drever et al, 2021; Watson et al, 2018) and provide multiple, synergistic benefits by maintaining existing carbon sinks and preventing large, potentially irrecoverable carbon emissions while providing biodiversity benefits (Arneth et al, 2020; Proctor, Schuster, Buxton, & Bennett, 2022). Protection can enable national and subnational strategies to more immediately maximize synergies between climate change mitigation and biodiversity goals, while also conserving other essential ecosystem services.…”
Section: Introductionmentioning
confidence: 99%